PROBLEMS OF THE EFFECTIVENESS OF REGULATORY LEGAL ACTS IN THE HEALTHCARE SYSTEM FOR MAINTAINING THE QUALITY OF ACTIVE LONGEVITY IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The article analyzes the institute of active longevity in the Republic of Kazakhstan, which has been called "antiaging" in science from the point of view of legal regulation of basic socio-economic directions. This covers, first of all, the health care system, social security, social services, etc. The article examines the socio-legal policy of the state on issues of ensuring a fruitful human life expectancy. The authors draw attention to the priority, from their point of view, directions of state policy in the field of regulation of healthy lifestyle issues and ensuring human life expectancy. Special attention is paid to the lack of legal regulation of the conceptual category of active longevity and its definitions in Kazakhstan. Attention is drawn to the fact that today in Kazakhstan there is no full-fledged, multidimensional legal framework, in addition, there is a clear need for a clear definition of the object of regulation in the sphere of these legal relations and the differentiation of hierarchy, that is, the levels of regulatory legal regulation. The article notes the need to conduct special research on increasing human life expectancy. The lack of organizational and legislative measures create the main difficulties in the practical implementation of the achievements of medical science in the practical life of the country. The scientific achievements available to medicine to prolong human life and maintain its quality are based primarily on the fight against diseases caused by aging, rather than on intervention in the aging process itself. The author emphasizes the latest achievements of scientists that genetically a person has a complex program to counteract aging. And without a theoretical understanding of the aging process and the identification of technologies to overcome the limit of human life expectancy, the whole complex of biomedical sciences, from the point of view of practice, may not be so effective without direct interaction with other branches of science and, above all, right‒wing science.Keywords. The Constitution of the Republic of Kazakhstan, active longevity, effectiveness of regulatory legal acts, standard of living, life expectancy, pension provision, health care system, current legislation.